Italian-Bangladeshi in London. A community within a community? - Della Puppa, Francesco (Migration Letters, 2021)
Based on a multi-sited ethnography in Italy and the United Kingdom, this contribution focuses on the onward migration of Italian-Bangladeshis to London, that is, Bangladeshi migrants who acquired EU citizenship in Italy and then moved to the British Capital. After the presentation of the reasons for this onward migration, the article will analyse the representation, constructed by the Italian-Bangladeshis interviewed in London, of the relationships between them (coming from different districts of Bangladesh) and the members of the “historical” British Bangladeshi community, in London since generations (originating primarily from the Bangladeshi district of Sylhet). Specifically, it will focus on the on mistrust – sometimes a fully-fledged hostility – between the two communities as it was narrated by the Italian-Bangladeshi respondents, framing it as a dichotomy between British citizens and (Southern) European citizens; as a wider dichotomy between residents of Bangladeshi origin in London, but originating from different regional contexts in Bangladesh; as an effect of the social stratification of the “Bangladeshi Diaspora” in the world.